Perencanaan Jadwal Perawatan Komponen Mesin Roll Forming Baja Ringan Untuk Meminimumkan Biaya Perawatan - Risky Lazuardi Irsyad; Siti Mundari (International Forum of Researchers and Lecturers, 2023)
PT. Nadha Karya Utama Indonesia, a company engaged in the manufacturing service industry that produces mild steel, located on Jl. Cold Hamlet, RT 04 RW 07, Ngronggot, Kab. Nganjuk, East Java. The purpose of this study is to plan the Roll Forming machine maintenance schedule in order to minimize maintenance costs. The method used in this study is using the Preventive Maintenance method. The calculation results obtain the reliability value of each component on the Roll Forming machine, namely 0.5 for the reliability of the Roll component, 0.5 for the Gear Box component, 0.5 for the Main Engine component, 0.46 for Bearings, and 0.5 for reliability Roll Stand. Determination of maintenance time intervals is based on Peventive Maintenance on Roll components for 37 days, Gear Boxes for 108 days, Main Machinery for 108 days, Bearings for 53 days, and Roll Stands for 146 days. Based on the calculation results, the total cost of maintenance before carrying out preventive with reliability is known to be Rp. 19,340,000, after carrying out preventive calculations with reliability is Rp. 13,120,139.10, it can be seen that before and after carrying out preventive calculations there is a difference in costs of Rp. 6,219. 860.9. From these results it is known that preventive maintenance can reduce the costs incurred by PT. Nadha Karya Utama Indonesia from before the Preventive Maintenance calculations were carried out.